2021
DOI: 10.1590/s1980-65742021022221
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of overtraining and motivation in elite soccer players

Abstract: This study aimed to monitor the behavior of the overtraining and motivations dimensions, as well as to verify whether these dimensions correlate in the preparatory and competitive periods over the season. Methods:Professional soccer players (n = 32) answered the Stress and Recovery Questionnaire for Athletes (RESTQ-Sport 76) and the Sport Motivation Scale (SMS) during the preparatory and competitive periods. Results: Intrinsic amotivation and sport-specific recovery were lower in the competitive period than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…The semi-structured interview was individual; each player received verbal guidance from the researcher and could answer the questions without a time limit (Fagundes et al, 2021). The data was collected through a semi-structured interview using questions about the occurrence of non-contact muscle injuries and psychological aspects in the last two seasons (2021)(2022).…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The semi-structured interview was individual; each player received verbal guidance from the researcher and could answer the questions without a time limit (Fagundes et al, 2021). The data was collected through a semi-structured interview using questions about the occurrence of non-contact muscle injuries and psychological aspects in the last two seasons (2021)(2022).…”
Section: Study Proceduresmentioning
confidence: 99%
“…Muscle injuries can be classified into two groups; direct muscle injuries (caused by external factors) and indirect muscle injuries (can also be referred to as "non-contact" and are caused by internal factors) that are identified as functional muscle disorders or structural muscle injuries (Mueller-Wohlfahrt et al, 2013). Consequently, muscle injuries have a negative impact on the physical and psychological health of soccer players (Fagundes et al, 2021). The incidence of muscle injuries in professional soccer teams is positively associated with economic costs, and inversely related to the team's success during the season (Ekstrand et al, 2023;Pulici et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Different technical, tactical, and contextual factors (e.g., scoring opportunities, ball possession, match status, penalty kicks, psychological aspects) are related to goal scoring in elite football (Li & Zhao, 2021;Pinheiro, Nascimento, Dicks, Costa & Lames, 2021;Rodenas, Malavés, Desantes, A. T., Ramírez, Hervás & Malavés, 2019;Aguado-Méndez, González-Jurado, Callejas-Jerónimo & Otero-Saborido, 2020;Fagundes, Costa, Reis, Pinheiro & Costa, 2021;Fagundes, Noce, Albuquerque, Andrade & Costa 2019). However, previous research has found that goal-scoring patterns are time-dependent (Kubayi y Toriola, 2019).…”
Section: Introductionmentioning
confidence: 99%